Evaluation of the Chagas Western Blot IgG Assay for the Diagnosis of Chagas Disease - Jean-Yves Brossas; Ballering Griselda; Margarita Bisio; Jeremy Guihenneuc; Julián Ernesto Nicolás Gulin; Stéphane Jauréguiberry; François-Xavier Lescure; Arnaud Fekkar; Dominique Mazier; Jaime Altcheh; Luc Paris (Pathogens, 2021)
Chagas disease is a debilitating and often fatal pathology resulting from infection by the protozoan parasite Trypanosoma cruzi. In its recommendations, the World Health Organization states that the diagnosis of T. cruzi infection is usually based on the detection of antibodies against T. cruzi antigens and performed with two methodologically different assays. An inconclusive result can be resolved with a third “confirmatory” assay. The objective of this article is to evaluate the effectiveness of the Chagas Western Blot IgG assay (LDBio Diagnostics, Lyon, France) as a confirmatory serologic test. The Chagas Western Blot IgG assay was performed with native antigens derived from a T. cruzi strain of the TcVI genotype. Retrospective sera were provided by two parasitology laboratories (France and Argentina). The sensitivity, specificity, positive predictive value and negative predictive value of the Chagas blot were all 100% in our sera collection. The Chagas blot is an easy and qualitative method for the diagnosis of Chagas disease, with results in less than 2 h. This immunoblot has potential as a supplemental test for the confirmation of the presence of antibodies against T. cruzi in serum specimens. Nonetheless, the very good initial results presented here will need to be confirmed in larger studies.